2017
DOI: 10.1186/s12886-017-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopy of pre-Descemet corneal dystrophy associated with X-linked ichthyosis: a case report

Abstract: BackgroundPre-Descemet corneal dystrophy (PDCD) is characterized by the presence of numerous, tiny, polymorphic opacities immediately anterior to Descemet membrane, which is a rare form of corneal stromal dystrophy and hard to be diagnosed. In vivo confocal microscopy (IVCM) is a useful tool to examine the minimal lesions of the cornea at the cellular level. In this article, we report a rare case of PDCD associated with X-linked ichthyosis and evaluate IVCM findings.Case presentationWe present a 34-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Careful inspection was performed in stromal images from the pre-endothelial region in all 16 subjects where full-thickness IVCM scans were available. It was observed that posterior keratocytes did not appear enlarged, nor did the microdots exhibit a clear localization to the cell nucleus or cell body (regardless of microdot grade), contrary to findings described in cases of pre-Descemet's membrane corneal dystrophy, [23][24][25] (Figure 3).…”
Section: Stromal Depth Dependence Of Central Corneal Microdotscontrasting
confidence: 74%
“…Careful inspection was performed in stromal images from the pre-endothelial region in all 16 subjects where full-thickness IVCM scans were available. It was observed that posterior keratocytes did not appear enlarged, nor did the microdots exhibit a clear localization to the cell nucleus or cell body (regardless of microdot grade), contrary to findings described in cases of pre-Descemet's membrane corneal dystrophy, [23][24][25] (Figure 3).…”
Section: Stromal Depth Dependence Of Central Corneal Microdotscontrasting
confidence: 74%
“…Approximately 90% of the patients with XLI are reported to harbor complete deletion of the STS gene and its flanking sequences, and a minority of patients has partial deletions and point mutations; however, the deletion pattern of the STS gene shows no significant correlation with the severity of cutaneous manifestations . It is reported that 8% of the patients with STS gene deletion are complicated with the deletions in the neighboring genes, thereby resulting in more complicated phenotypes, such as microsomia, chondrodysplasia punctata, Kallmann syndrome, ocular albinism, epilepsy, electroencephalography abnormality, mental retardation, hyposmia, attention deficit hyperactivity disorder, autism, and language development disorder …”
Section: Discussionmentioning
confidence: 99%
“…The hyperreflective particles scattered in the middle-posterior stroma identified with FD-OCT are consistent with those found in PDCD-affected humans [ 19 , 20 ]. Hyperreflective keratocyte intracellular/extracellular deposits increasing in density towards the posterior stroma and enlarged keratocytes are characteristic IVCM features of PDCD in humans [ 19 21 ]. As PDCD does not affect vision thereby not requiring surgical intervention, the pathology of this disorder is neither well-established nor clearly confirmed hereditary despite its classification as a dystrophy in humans [ 22 ].…”
Section: Discussionmentioning
confidence: 99%